Biblical cartography and the (mis)representation of Paul"s missionary travels - Guijarro Oporto, Santiago (HTS teologiese studies, 2019)
Biblical cartography has elaborated a master narrative of Paul’s missionary activity. This master narrative, which clearly distinguishes between three different journeys, is omnipresent and can easily be found in Bibles and atlases. Nevertheless, Paul’s letters and the book of Acts do not support such a clear distinction. The present study contends that the distinction between three missionary journeys is a modern construct and that this way of representing Paul’s missionary activity has a significant impact on how we understand it. By representing Paul’s missionary activity as an orderly sequence of three travels, the maps not only minimise the novelty of his independent mission but also minimise Paul’s confrontation with the Jerusalem church. In this representation, he is no longer the marginal leader of a minority movement within the nascent church, but ‘the’ missionary. The portrayal of the missionary activity of Paul in biblical maps is an example of the uncritical transfer of exegetical traditions, and of the role of these traditions in the creation of a master narrative of Christian origins.